High Birth Weight Is a Risk Factor of Dental Caries Increment during Adolescence in Sweden - Annika Julihn; Ulrika Molund; Emma Drevsäter; Thomas Modéer (MDPI AG, 2014)
This study aimed to assess whether birth weight is associated with dental caries during the teenage period. In this register-based cohort study, all children of 13 years of age (n = 18,142) who resided in the county of Stockholm, Sweden, in 2000, were included. The cohort was followed until individuals were 19 years of age. Information regarding dental caries was collected from the Public Health Care Administration in Stockholm. Data concerning prenatal and perinatal factors and parental socio-demographic determinants were collected from the Swedish Medical Birth Register and National Registers at Statistics Sweden. The final logistic regression model showed that birth weight ≥4000 g, adjusted for potential confounders, was significantly associated with caries increment (DMFT ≥ 1 (D = decayed, M = missing, F = filled, T = teeth)) between 13 and 19 age (OR, 1.22; 95% CI = 1.09-1.36). The relatively enhanced risk OR was further increased from 1.22 to 1.43 in subjects with birth weight ≥4600 g. On the contrary, subjects with birth weight <2500 g exhibited a significantly lower risk (OR, 0.67; 95% CI = 0.50-0.89) for exhibiting caries experience (DMFT ≥ 4) at 19 years of age. In conclusion, high birth weight can be regarded as a predictor for dental caries, and especially, birth weight ≥4500 g is a risk factor for caries increment during adolescence.